Generalized Commuting Mapping in Prime and Semiprime Rings - Mahmood, Auday Hekmat (Iraqi Journal of Science, 2022)
Let R be an associative ring. The essential purpose of the present paper is to introduce the concept of generalized commuting mapping of R. Let U be a non-empty subset of R, a mapping   : R  R is called a generalized commuting mapping on U if there exist a mapping :R R such that =0, holds for all U. Some results concerning the new concept are presented.